Hepatocyte gap junctions are permeable to the second messenger, inositol 1,4,5-trisphosphate, and to calcium ions. - Sáez, J C (1989)
Hepatocytes are well coupled by gap junctions, which allow the diffusion of small molecules between cells. Although gap junctions in many tissues are permeable to molecules larger than cAMP and in several preparations gap junctions pass cAMP itself, little direct evidence supports permeation by other second-messenger species. Ca2+, perhaps the smallest second messenger, would be expected to cross gap junctions, but the issue is complicated because gap-junction channels are closed when intracellular free Ca2+ concentration, [Ca2+]i, is elevated to micromolar levels or above. Inositol 1,4,5-trisphosphate (InsP3), a second messenger that can evoke Ca2+ release, might also reduce junctional permeability by this mechanism. We report here evidence for transjunctional flux of Ca2+ and InsP3 in freshly isolated pairs or small clusters of rat hepatocytes. The Ca2+ indicator fura-2 was used to monitor transjunctional diffusion of Ca2+ directly or to detect passage of InsP3 by localized Ca2+ release. Fura-2 injected as the free acid passed between cells. Injection of InsP3 or CaCl2 immediately increased [Ca2+]i in the injected cell (peak values less than 1 microM), and [Ca2+]i increased rapidly in contacting cells (within seconds). The initial rise in [Ca2+]i induced by InsP3 was greater at discrete regions in the cytoplasm of both injected and uninjected cells and was inconsistent with simple diffusion of Ca2+. In the coupled cells the regions of greatest increase were not necessarily near the contact zone. In contrast, the rise induced in [Ca2+]i by CaCl2 injection when cells were bathed in normal Ca2+ was always more diffuse than with InsP3 injection, and in cells coupled to a cell injected with CaCl2 the earliest and maximal increases occurred at the region of cell contact. This difference in distribution indicates that injected InsP3 (or an active metabolite, but not Ca2+) diffused between cells to cause localized release of Ca2+ from intracellular stores. Ca2+ injection induced a rise in [Ca2+]i in coupled cells even when cells were maintained in Ca2+-free saline, suggesting that changes in [Ca2+]i seen in adjacent cells were due to transjunctional diffusion from the injected cell and not to uptake from the extracellular solution. However, in Ca2+-free saline, [Ca2+]i distribution was nonuniform, indicating that Ca2+-releasing mechanisms contribute to the observed changes. No increase in [Ca2+]i was seen in adjacent cells when Ca2+ was injected after treatment with the uncoupling agent octanol (500 microM), which itself did not change [Ca2+]i. These data provide evidence that the second messengers Ca2+ and InsP3 can be transmitted from cell to cell through gap junctions, a process that may have an important role in tissue function.